2011
DOI: 10.1038/oby.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Lipid Abnormalities by α‐Lipoic acid Through Antioxidative and Anti‐Inflammatory Effects

Abstract: Recent data have revealed that oxidative products and inflammatory mediators are increased in the insulin-resistant states of obesity and type 2 diabetes mellitus (T2DM). Obese patients with impaired glucose tolerance (IGT) are at high risk for developing T2DM and have high incidence of dyslipidemia. α-Lipoic acid (ALA) is a potent antioxidant with insulin sensitizing activity. However, it is not clear whether ALA is effective on lipid parameters in humans. This study has investigated 22 obese subjects with IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
65
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 40 publications
12
65
0
7
Order By: Relevance
“…Our results demonstrated that LA induced a time-dependent inhibition of JNK phosphorylation, which might suggest the Supplemental Material can be found at: ( 13,61 ). In this context, we and others have demonstrated that dietary supplementation with LA reduces weight loss and fat mass without increasing circulating FFA and improves insulin resistance in rodents ( 10,62,63 ) and in humans ( 7 ), and, as previously suggested, this could be associated with LA-induced fatty acid oxidation. In this context, our experimental data support the notion about the ability of LA to promote fatty acid oxidation in 3T3-L1 adipocytes (supplementary Fig.…”
supporting
confidence: 58%
“…Our results demonstrated that LA induced a time-dependent inhibition of JNK phosphorylation, which might suggest the Supplemental Material can be found at: ( 13,61 ). In this context, we and others have demonstrated that dietary supplementation with LA reduces weight loss and fat mass without increasing circulating FFA and improves insulin resistance in rodents ( 10,62,63 ) and in humans ( 7 ), and, as previously suggested, this could be associated with LA-induced fatty acid oxidation. In this context, our experimental data support the notion about the ability of LA to promote fatty acid oxidation in 3T3-L1 adipocytes (supplementary Fig.…”
supporting
confidence: 58%
“…LA has powerful antioxidant properties and is therefore suitable for the treatment of diseases related to oxidative stress; for example, short-term and long-term supplementation of LA (200-1800 mg/day) in type 2 diabetic patients have beneficial effects in maintenance of glycemic control (200). LA can exert beneficial effects by several mechanisms, including improvement in vascular endothelial cell function (257), decrease in inflammation (104), amelioration of lipid abnormalities (376), and protection against myocardial ischemia/reperfusion injury (341) or antihypertensive effects (83). Defects in LA biosynthesis in human subjects can lead to the development of mitochondrial diseases, as has been shown in children with a mutation of NFU1, which is necessary for maturation of proteins such as succinate dehydrogenase or lipoic synthase (215).…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 99%
“…LA has been used therapeutically in diabetic neuropathy and retinopathy (1, 6, 19, 33, 36, 38, 46, 49 -52), but its TG-lowering properties have only recently been recognized, first in laboratory animals (7,22,43,47) and then in humans (27,48). LA is a naturally occurring, essential, dithiol-containing cofactor synthesized enzymatically from octanoate in most prokaryotic and eukaryotic micro-organisms as well as plant and animal mitochondria (15).…”
mentioning
confidence: 99%